Governance Breakdown dan Ketegangan Sosial Ekologis: Implementasi Perlindungan Kawasan Penyangga Cagar Alam Cycloop Kabupaten Jayapura - Daud Balli; Agustinu Fatem; Yosephina Ohoiwutun; Vince Tebay (JURNAL EKOLOGI BIROKRASI, 2025)
This study aims to analyze the implementation of the protection and management policy for the Cycloop Mountains Nature Reserve buffer zone in Jayapura by highlighting the issues of governance breakdown and socio-ecological tensions resulting from the weak institutionalization of customary legitimacy. The study employed a qualitative approach with a case study design, through in-depth interviews, Focus Group Discussions (FGDs), participant observation, and documentation studies involving the government, indigenous communities, migrant communities, non-governmental organizations, and academics. Data were analyzed thematically using NVivo with a Systems Theory framework, Grindle's content-context approach, and the Edwards III implementation model. The results indicate that the failure of the Cycloop buffer zone policy implementation is caused by institutional fragmentation, overlapping authority, weak cross-sectoral coordination, limited resources, and low-effectiveness of policy communication. In addition, the lack of integration of customary legitimacy and local knowledge into formal policies weakens social legitimacy and triggers conflicts over resource utilization between conservation interests and community economic needs. This condition creates a negative feedback loop that accelerates the ecological degradation of the buffer zone and impacts community social welfare. This study concludes that protecting the Cycloop buffer zone requires more inclusive and adaptive governance reforms through strengthening institutional coordination, recognizing customary legitimacy, and implementing a community-based conservation approach to ensure ecosystem sustainability and social justice.